Deletion analysis on multidrug resistant Mycobacterium tuberculosis in Portugal - Silva, Carla (2012)
Deletion analysis on multidrug-resistant Mycobacterium tuberculosis in Portugal Carla Silva1,4, João Perdigão1, Isabel Couto2,3, Miguel Viveiros2,5, Luísa Jordão4 and Isabel Portugal1 1URIA, Centro de Patogénese Molecular, Faculdade de Farmácia da Universidade de Lisboa, 2Unit of Mycobacteriology, Instituto de Higiene e Medicina Tropical, Universidade Nova de Lisboa (IHMT/UNL), 3Centro de Recursos Microbiológicos (CREM), Faculdade de Ciências e Tecnologia, 4Departamento de Doenças Infecciosas, Instituto Nacional de Saúde Dr Ricardo Jorge, 5COST ACTION BM0701 (ATENS) Portugal is one of the European countries with the highest incidence of tuberculosis (TB), with a notification rate higher than 20/100 000 inhabitants. One of the biggest threats to TB control is the emergence of infection case with features of multidrug resistance (MDR-TB) and extensive drug-resistance (XDR-TB) TB. Most strains of MDR-TB circulating in the Lisbon area belong to a particular family of genetically related strains, the Lisboa family, detected in the 90’s. The prevalence of this family of strains has increased over the years, and represented more than 85% of the MDR-TB strains in the year of 2008. XDR-TB has been recently derived from MDR-TB strains and account for about 50% of these, the majority belonging to Lisboa family. Lisboa family represent a serious problem regarding TB control in Portugal and its prevalence in recent years suggests that these strains may have selective advantages over others. In an attempt to define the evolutionary origin and the identification of factors that favors the continued existence and spread of Lisboa strains in the Portuguese setting, genomic deletions in seven MDR-TB clinical isolates representative of the principal clusters circulating in Portugal were studied. Previously characterized by 24 loci MIRU-VNTR, the isolates were analyzed for the presence or absence of the genomic regions pks15/1, RD105 and RD174. We verified that five of the 7 isolates analyzed belong to the Euro American Lineage, with the 7bp deletion on pks15/1 gene, with other two belonging to the East-Asia Lineage (including the Beijing family strains), characterized by the presence of an intact pks15/1 gene and absence of RD105 region. Further analysis of the Euro American Lineage strains revealed that four strains, including the two representative strains of Lisboa family, present the same second genomic deletion – RD174, a marker for the sublineage West Africa; the remaining isolate is still under study, and more analysis are ongoing. We conclude that the circulating strains present some lineage diversity, with the predominant strains, Lisboa family, belonging to the West Africa Sublineage. Such, may be indicative of selective advantages and/or better adaptation to the host population in the presence of circulating Beijing strains.